2023
DOI: 10.32920/ryerson.14647110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regionalization of Immigrant Settlement in Ontario : Exploring Experiences of Small and Medium Sized Reception Centres

Abstract: This paper explores the regionalization of immigrant settlement in Canada’s smaller cities which has not been sufficiently addressed in Canada’s largest province, Ontario. The paper investigates this through a comprehensive review of the existing Canadian literature and research into the changing volume of immigrant settlement and the social geography of Ontario’s smaller cities from 1996 to 2015. This research is conducted through the development of a categorization system which orders Ontario’s CMAs into tie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Well-known places get the highest number of immigrants because immigrants go to places with which they are familiar (Bégin-Gillis, 2010). Smaller centers must therefore make themselves stand out, using platforms and methods that reach immigrant populations (Goodbrand, 2015). For example, websites and other marketing tools, such as overseas attraction fairs, can be used to provide immigrants with positive perceptions of smaller centers in a bid to attract them (Bégin-Gillis, 2010).…”
Section: Factors That Attract and Retain Immigrantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-known places get the highest number of immigrants because immigrants go to places with which they are familiar (Bégin-Gillis, 2010). Smaller centers must therefore make themselves stand out, using platforms and methods that reach immigrant populations (Goodbrand, 2015). For example, websites and other marketing tools, such as overseas attraction fairs, can be used to provide immigrants with positive perceptions of smaller centers in a bid to attract them (Bégin-Gillis, 2010).…”
Section: Factors That Attract and Retain Immigrantsmentioning
confidence: 99%
“…Immigrants living in smaller centers are less at risk of unemployment and low earnings than their counterparts living in large centers (Goodbrand, 2015). A survey conducted in regional and rural Australia found that immigrants in nonmetropolitan areas had positive labor market experiences, including a high rate of economic participation, a short time span to secure a first job, and few problems finding work (Krivokapic-Skoko & Collins, 2016).…”
Section: Employment Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation